Pengaruh Kompensasi dan Komitmen Karyawan Terhadap Kinerja Karyawan Divisi Telemarketing Area 1 DKI Jakarta di PT. Sedaya Finance (Astra Credit Companies) - Vina Eka Putri; Hasanah Hasanah (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effect of compensation and employee commitment on employee performance in the Telemarketing Division Area 1 DKI Jakarta at PT Astra Sedaya Finance (Astra Credit Companies). This research employed a quantitative method with a descriptive and verificative approach. The population consisted of all telemarketing employees, and a saturated sampling technique was applied. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that compensation has a positive and significant effect on employee performance. Employee commitment also has a positive and significant effect on employee performance. Simultaneously, compensation and employee commitment significantly influence employee performance. These findings suggest that improving fair compensation systems and strengthening employee commitment can enhance employee performance effectively. This study is expected to provide managerial insights for human resource management practices.